2011
DOI: 10.1186/1745-6215-12-5
|View full text |Cite
|
Sign up to set email alerts
|

The cameroon mobile phone sms (CAMPS) trial: a protocol for a randomized controlled trial of mobile phone text messaging versus usual care for improving adherence to highly active anti-retroviral therapy

Abstract: BackgroundThis trial aims at testing the efficacy of weekly reminder and motivational text messages, compared to usual care in improving adherence to Highly Active Antiretroviral Treatment in patients attending a clinic in Yaoundé, Cameroon.Methods and DesignThis is a single-centered randomized controlled single-blinded trial. A central computer generated randomization list will be generated using random block sizes. Allocation will be determined by sequentially numbered sealed opaque envelopes. 198 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 29 publications
2
42
1
1
Order By: Relevance
“…The Cameroon Mobile Phone SMS trial focused on ensuring compliance with antiretroviral treatment in patients from Cameroon. 23 This study confirmed that mobile telephones were an effective tool for remaining in contact with patients. The importance of biobanks in health development is understood in Africa.…”
Section: Discussionsupporting
confidence: 83%
“…The Cameroon Mobile Phone SMS trial focused on ensuring compliance with antiretroviral treatment in patients from Cameroon. 23 This study confirmed that mobile telephones were an effective tool for remaining in contact with patients. The importance of biobanks in health development is understood in Africa.…”
Section: Discussionsupporting
confidence: 83%
“…To date, published literature of larger studies using SMS has focused on antiretroviral therapy adherence for patients with HIV/AIDS, including sending a text message asking “how are you?” 37 and sending automatic text medication reminders. 12,14 A study protocol outlined how researchers proposed to use reminders with a motivational message, 38 but do not describe how the motivational messages were designed.…”
Section: Discussionmentioning
confidence: 99%
“…Details can be obtained from the published protocol [13]. Using a parallel group design, eligible and consenting patients were randomized to intervention and control arms with a 1∶1 allocation ratio.…”
Section: Methodsmentioning
confidence: 99%